Stability analysis of transmission tower foundations in permafrost equipped with thermosiphons and vegetation cover on the Qinghai-Tibet Plateau. (June 2018) - Guo, Lei; Zhang, Zhongqiu; Wang, Xinbin; Yu, Qihao; You, Yanhui; Yuan, Chang; Xie, Yanli; Gou, Tingtao
Highlights: The application results of thermosiphons at foundation soils were studied. Ponding in the excavation pits and water infiltration threaten the tower stability. The use of vegetation can help enhancing tower stability along with thermosiphons. The backfilling of frozen blocks to the excavation pits should be avoided. Abstract: During the construction of the ±400 kV direct current power transmission line (DCPTL), frozen blocks were backfilled into the foundation pits in permafrost regions because of the lack of backfilling materials and other problems, but this resulted in less compact backfilled soils. To ensure the stability of the tower foundations, a large number of thermosiphons were installed. This study discusses the threat to the stability of tower foundations of water infiltration along the large voids created within the backfilled soils by the use of frozen blocks, and quantifies the efficacy of a combination of thermosiphons and vegetation cover in enhancing tower stability, based on field collected data from January 2011 to April 2017. The results indicate that the cooling effects of thermosiphons caused a large amount of net heat removal from the foundation soils, even during the first operational year of the foundation, while foundation soils without thermosiphons exhibited net heat input during the same period. Ponding in the pits and downward infiltration of water obviously work to warm the foundation soils, and can result in the settlement of the tower footings, threatening the tower stability. The combination of thermosiphons and vegetation cover is shown to effectively cool the foundation soils and to reduce the settlement of the footings, thus ensuring the continued tower stability. This study also shows that the backfilling of frozen blocks should be avoided in the current climate conditions, even though effective cooling measures like thermosiphons are used because the downward infiltration of water along the large voids between the frozen backfilled blocks can't be totally prevented. If the current degradation of the frozen state of the backfilled soils continues, the infiltrated water, which has been frozen at the bottom of the backfill, will begin to thaw again, threatening the stability of the tower foundations.